Pattern of symptoms and symptomatic treatment in adults and the aged population: a retrospective analysis of advanced cancer patients followed at home. (3rd May 2016) - Mercadante, Sebastiano; Aielli, Federica; Masedu, Francesco; Valenti, Marco; Verna, Lucilla; Mercadante, Alessandro; Porzio, Giampiero
Abstract: Context Data regarding symptom burden and symptomatic drugs in palliative population in different classes of age are lacking. Objective The aim of this retrospective study was to assess the symptom burden, and the profile of symptomatic drugs in the last four weeks of life in adults and older cancer patients followed at home. Methods Charts of 412 patients were retrospectively analyzed by using a backward analysis. Patients were divided into three groups: adults (<65 years, A), old (65–74 years, O1), very old (75–84 years, O2), and the oldest (≥85 years, O3). Results At -4W Karnofsky status was significantly lower for older people ( p = 0.03). No significant effect of age on the vector of symptoms was found ( p = 0.07). A significant decrease in intensity of pain and nausea, and an increase in intensity of all other symptoms was found through the four weeks of the study ( p = 0.00). No differences of drug pattern among the age categories were found. The use of symptomatic drugs decreased over time, except for opioids. Age statistically affected NSAID use, neuroleptic use, and antiemetics over time. Conclusion The burden of symptoms worsened in the last four weeks of life, except for pain and nausea, but did not differ among the age subgroups. The use of NSAIDs, neuroleptics, and antiemetics changed, while the frequency of opioid use was unchanged until death.